Microplastic contamination in s. Cucullata and associated health risk assessment in the strait of Malacca - Ghazali, Intan Noor Munira; W. Johari, Wan Siti Mardhiah; Faudzi, Fikriah; Yusof, Fitri; Razali, Azaima; Hassan, Artika; Ramli, Muhammad Zahir; Kasmuri, Norhafezah; Miskon, Mohd Fuad (2023)
Saccostrea cucullata, also known as rock oysters, are chosen as the targeted organisms on rocky shores to elucidate the pathway of microplastics in sessile organisms. Eight rocky shores along the Strait of Malacca located on the coastal waters of the Malaysian states of Johor, Melaka, and Negeri Sembilan were selected. A total of 65 particles were discovered, of which 58.5 percent was identified as polymers. The microplastic abundance was between 0.0302 to 0.3586 microplastic items/wet weight and 0.1053 to 0.6000 microplastic items/individual S. cucullata. The microplastics found was typically filament-shaped, black in colour, and ranging in size from 107.85 µm to 14614.43 µm. With the exception of Teluk Kemang, the hazard quotient (HQ) values for all of the sampling sites were unacceptable and exceeded 1. The information gathered could serve as the starting point for further research into microplastics contamination of the marine environment and its inhabitants in Malaysia.